CRUTAC: a história da Extensão Universitária da UFMA no município de Codó no período de 1972 a 1979 - SILVA, José Augusto Medeiros (2013)
Analysis of Stocks Rural Center University Training and Community Action (CRUTAC)/ Codo, in the period 1972-1979. This research is part of the trend "Institutions School, knowledge and educational practices," in the Group "History and Memory of education in Maranhão", Post-Graduation Program in Education at the Federal University of Maranhão (UFMA). We aim at identifying whether the actions were developed in integrated interdisciplinary teaching and research and if they contributed to the training and development of university education in the city. Our specific goals are: to analyze the socioeconomic and political context in the city of Codo, after the implementation of CRUTAC; investigate the factors that contributed for the choice of Codo for the implementation of the second unit of CRUTAC and verify the impact of such unity to the community. To reach these goals we adopted a qualitative methodological procedure of research (literature and documents). Along this process, we analyzed official documents: laws, decrees, resolutions, ordinances, agreements, and others as newspapers, dissertations, monographs, reports and dossiers. We conducted interviews with former General Coordinator of CRUTAC/MA, teachers and community leaders in order to measure the impact of the program for the community of Codo. The research was focused in some authors on the subject, such as, Gurgel (1986), Freire (1985) and Saviani (1981), among others. Given the number of actions taken by CRUTAC / Codo, we chose those that were implemented in the Neighborhoods of São Francisco and São Sebastião. We can conclude that the impact of the actions of CRUTAC for the population of Codo was positive givent the fact that the community itself claimed for the return of such experience. However, the actions we refer to did not express an effective interdisciplinary among teaching and research. We hope, finally, that this work may bring important contributions to the area of history of education, in particular to University Extension.